Mining, Money and the Internal Market in Eighteenth Century Brazil - Alves Carrara, Angelo (Revista Complutense de Historia de América, 2012)
By 1744, almost all the gold deposits in Minas Gerais had been discovered and in 1732 diamond mining was also initiated there. Besides contributing to a significant shift of population within the Portuguese Empire, the mining centres also became important points of articulation between large areas of the colony. Brazil began to be drawn on the maps as we know it today. One of the most notable consequences was the displacement of the most important port of Brazil, Salvador, to Rio de Janeiro. This paper aims to present the effects produced by the extraction of minerals in Brazil, on agriculture, cattle-raising and the movement of goods. The study period extends from the late seventeenth century, when the exploitation of the most important Brazilian gold mines of Minas Gerais began, until the arrival of the Portuguese court at Rio de Janeiro in 1808.